Nilai-Nilai Adab Seorang Pendidik Menurut Buku Kepribadian Pendidik Dalam Al-Qur’an Karya Hifza Hamdan - Nori (Tarbiya Islamica, 2023)
This research is motivated by the book Personality of Educators in the Qur'an by Hifza Hamdan which offers the concept of education and the personality of an educator, as well as its relevance to the reality of education today, is a form of scientific endeavor that can be expected to have many values, one of which is related to education adab. The purpose of this study is to describe and analyze: 1) Adab values ​​that must be possessed by an educator in the book Personality of Educators in the Qur'an by Hifza Hamdan. 2) Implementation of the educational values ​​of an educator in the Personality of Educators in the Qur'an by Hifza Hamdan. This study uses a qualitative approach with the type of literature study (library research). The data source used in this study is the text in the book Personality of Educators in the Al-Qur'an Its Relevance to Contemporary Reality by Hifza Hamdan, then the data collection technique uses document analysis. The data analysis technique used is content analysis. Based on the results of the analysis carried out, the results of this study are: 1) The values ​​of etiquette that must be possessed by an educator in the book Personality of Educators in the Al-Qur'an by Hifza Hamdan, are as follows: a) Have wisdom; (honest, consistent (istiqomah), intelligent (fatanah), trustworthy (amanah) and convey (tabligh), b) Sincerity c) Humble d) Learner, e) Tolerant and appreciative, f) Compassionate and compassionate, g) Wise , h) Generous and commendable, i) Forgiving and forgiving, j) Speaks kind words and touches the soul, k) Patient and steadfast, l) Creative and innovative, m) Dignified and charismatic, n) Devotion spirit, o), Capable set an example. 2) Implementation of the Adab Values ​​of an Educator in the Personality of Educators in the Al-Qur'an by Hifza Hamdan, namely as educators as caregivers, educators-educators, educators as caregivers, educators as guides (givers of instructions), educators as protectors, educators as teachers and educators as experts in science.